Sex Education in Teenagers About Puberty, Sexual Development And Sexual Harassment - Trilia, Trilia; Nambiar, Nisha; Said, Faridah Mohd (Journal of Neonatal Surgery, 2025)
Sex education is knowledge taught about matters related to gender, including the growth of the sexes (male or female), the function of the sexes as reproductive organs, development in women and men, menstruation, wet dreams, and so on, to the emergence of lust due to changes in hormones. This study is to describe the results of a literature review on sex education about puberty, sexual development and sexual harassment in adolescents. This study uses a literature review method, identifying literature through searches in the Google Scholar and PubMed databases and obtaining 10 journals that meet the inclusion criteria. This literature review shows that sex education should be given as early as possible to adolescents as a provision in facing changes that occur in themselves and the environment. Sexual harassment is more often committed by male adolescents. The provision of sex education to adolescents is influenced by parents, teachers and the surrounding environment. The selection of materials regarding sex education is very important to prevent confusion in changes and development from childhood to adulthood. Providing sexual education related to puberty, sexual development and sexual harassment in adolescents from an early age is an important thing that must be done as a provision in facing changes that occur in themselves and their environment and the need for supervision of adolescents in getting topics related to sexuality, which can influence the attitudes and lives of adolescents.